Influência de fatores ambientais e dos níveis de microrganismos potencialmente cariogênicos no desenvolvimento da cárie precoce da infância - Ribas, Lais Fernanda Fonseca [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Early childhood caries (ECC) is a microbial infection that can severely affect the teeth of young children. The objectives of this study were to evaluate the influence of environmental factors (diet, hygiene, socioeconomic and cultural conditions) and the levels of potentially cariogenic microorganisms in the development of the ECC. 36 to 60 month-old children were selected to participate in this study. Children were grouped into: Caries Free group (CF, n=32), ECC group (n=25) and severe ECC group (S-ECC, n=33). Saliva and dental biofilm samples were collected from children to compare the levels of mutans streptococci and lactobacilli using culture method. Saliva was also evaluated to detect and quantify the following microorganisms: Streptococcus mutans, Streptococcus sobrinus and Lactobacillus spp. by quantitative PCR (qPCR). Data about diet, oral hygiene, socioeconomic and cultural conditions were obtained by questionnaire and diet diary with the parents. Data were analyzed statistically considering p≤ 0.05. The results showed that S-ECC children had significantly lower income and lower educational level of their parents. Considering diet diary, children with S-ECC had longer breastfeeding and higher age at onset of artificial feeding. Microbiological data showed higher count of mutans streptococci in saliva of S-ECC children compared with the others groups. It was also noted by qPCR higher prevalence and quantity of S. mutans and S. sobrinus in saliva of S-ECC children. There was no difference in relation to lactobacilli levels for culture method and qPCR. It was concluded that there was influence of socio-economic and cultural risk factors, breastfeeding and levels of S. mutans and S. sobrinus in the severity of the ECC

A cárie precoce da infância (CPI) é uma infecção microbiana que pode afetar severamente a dentição de crianças jovens. Os objetivos desse estudo foram avaliar a influência de fatores ambientais (dieta, higiene, condições socioeconômicas e culturais) e dos níveis de microrganismos potencialmente cariogênicos no desenvolvimento da CPI. Crianças de 36 a 60 meses foram selecionadas para participarem do estudo. Elas foram distribuídas em: grupo crianças livres de cárie (LC, n=32), grupo CPI (n=25) e grupo CPI severa (CPI-S, n=33). Amostras de saliva e biofilme foram coletadas das crianças para comparar os níveis de estreptococos grupo mutans e de lactobacilos utilizando o método de cultura. A saliva também foi analisada por PCR quantitativoqPCR) para detecção e quantificação dos seguintes microrganismos: Streptococcus mutans, Streptococcus sobrinus e Lactobacillus spp. Dados sobre dieta, higiene, condições socioeconômicas e culturais foram obtidos por meio do preenchimento do questionário e diário de dieta com os responsáveis pela criança. Os dados foram analisados estatisticamente, considerando p≤ 0.05. Os resultados obtidos mostraram que as crianças com CPI-S apresentaram significativamente menor renda familiar e menor nível cultural do responsável. Quanto à dieta, as crianças com CPI-S apresentaram maior tempo de amamentação materna e maior idade no início da amamentação artificial. Os dados microbiológicos mostraram maior contagem de estreptococos grupo mutans na saliva e biofilme das crianças com CPI-S em comparação com os demais grupos. Também foi notado por qPCR maior prevalência e quantidade das espécies S. mutans e S. sobrinus na saliva das crianças com CPI-S. Não houve diferença entre os grupos para os níveis de lactobacilos por cultura e por qPCR. Conclui-se que...
Keywords: Cárie dentária; Streptococcus mutans; Streptococcus sobrinus; Lactobacillus; Dental caries